Mathematical land use theory - Papageorgiou, G. J. (Lexington, Mass. : Lexington Books, 1976)
The text is in two parts. The first part contains three general statements related to mathematical land use theory. The second contains fifteen chapters related to specific problems in the field.
"A coded bibliography of the new urban economics, compiled by A. Anas and D. S. Dendrinos": p. 293-307.
ne 24/01/2019
Loans
Keywords: Urban economics; Land use; Regional planning